Investigation into the Determinants of Cross-Sectional Variation in the CDS-Bond Basis - Epps, Adrian G (2014)
This paper examines the CDS-Bond basis on S&P 100 reference entities in the period 2009-14. Specifically, this paper seeks to explain the cross-sectional variation in basis levels displayed by these entities. With few exceptions, prior work focuses on the aggregated basis level and what might cause this to deviate from the theoretical zero level. I choose to extend the literature by focusing on disaggregated data, on the individual basis levels of specific reference entities, and investigate why there is such significant disparity around the mean basis level. This paper finds that a vast proportion of cross-sectional variation in basis levels can be attributed to differentials in bond specific liquidity measures and disparity in funding related limits to arbitrage.